IMPROVING STUDENTS’ UNDERSTANDING ON SIMPLE PRESENT TENSE THROUGH AUCTION GRAMMAR GAME AT THE EIGHTH GRADE STUDENTS OF SMP KATOLIK BELIBIS MAKASSAR - Adriani Jihad (Universitas PGRI Semarang, 2021)
This research aimed to find out the Auction Grammar Game in improving students’ understanding on simple present tense. This research used pre-experimental method. The population of this research was the whole eighth grade students of SMP Katolik Belibis Makassar which consists of 29 students. By using total sampling technique, this class was taken as a sample which consists of 29 students. Sample of this research was the same with the population because there was only one class for the eighth-grade students of SMP Katolik Belibis Makassar. The data were analyzed by using SPSS Program. The result of this research found that students’ understanding on simple present tense was improved significantly. It can be seen in the result of the students’ mean score in post-test that was higher than pre-test (78.79>35.52). in addition, t-test value was higher than t-table (20.657>2.048). It can be concluded that the Auction grammar game improves students’ understanding on simple present tense.